Decentralizing Indonesia : A Regional Public Expenditure Review Overview Report - World Bank (Washington, DC, 2013)
Indonesia has embarked upon a radical and rapid decentralization program. Regional autonomy is transforming one of the most centralized countries in the world into one of the more decentralized ones. If managed well, a country as large and diverse as Indonesia will benefit greatly from decentralization, through more efficient service delivery, but also national unity and democracy. Yet, not all is well. The Consultative Assembly, the country's highest constitutional body, has recognized as much by calling for a thorough evaluation of the decentralization program, and adjustments of the decentralization laws, if needed. Indonesia should use the process of revision as an opportunity to create a consensus on the type and extent of regional autonomy, and define better rules of the game to ensure that the benefits of decentralization will prevail. Rapid decentralization and its hasty preparation have left much unfinished business. Some of the issues encountered are merely teething problems of an ambitious decentralization program, and over time they can be ironed out. Others could jeopardize the success of the program itself, undermine the potential efficiency gains of decentralization, and even trigger fiscal imbalances and macroeconomic instability over the longer run. These issues fall into three broad categories: (i) the assignment of functions over levels of government: (ii) local capacity to implement the functions; (iii) the intergovernmental fiscal system; and (iv) accountability at the local level.